Implementation of Civil Servant Functional Position Regulations from a Justice and Welfare Perspective - Bayu Adji Dwi Kuncoro; Rodiyah Rodiyah (Semarang State University Undergraduate Law and Society Review, 2025)
Lemdiklat Akpol there is a discrepancy in the alignment between government regulations and police regulations in Indonesia. Career patterns have various very important roles in an agency for the development of an employee's career because they have an impact on the level of expertise and professionalism of employees individually or their performance in an agency. This article aims to describe and analyze the retirement age related to the functional position of Civil Servants from the perspective of justice and welfare at the Police Academy education and training institution. The study uses a qualitative legal approach, non-doctrinal research type (Sociological Juridical), data collection techniques using interviews, observations, and document studies, data validity Triangulation and data analysis using data reduction, data presentation and conclusions. The results of the study show that Lemdiklat Akpol applies a retirement age of 58 years even though there is a regulation from Menpan RB which is 65 years for functional lecturers. The application of the retirement age at Lemdiklat Akpol refers to the Police Law although there are still problems of discrepancy and inconsistency between government regulations and regulations in the Police.